INFLUENCE OF INSTITUTIONAL OWNERSHIP, CAPITAL INTENSITY, AND FINANCIAL DISTRESS ON TAX AGGRESSIVENESS - Ariyati, Vievi; Indriani, Agustina (STIE Jambatan Bulan, 2025)
This research aims to test and analyze the influence of institutional ownership, capital intensity and financial distress on tax aggressiveness. The population used in this research is energy sector companies listed on the IDX in 2020-2024. The sampling technique used in this research was purposive sampling, so that 105 samples were obtained. Data were analyzed using panel data linear regresion via Eviews 12. The results of this study indicate that institutional ownership has an effect on tax aggressiveness, capital intensity has no effect on tax aggressiveness and financial distress have no effect on tax aggressiveness. This research concludes that the greater the institutional ownership, the lower the company's tax aggressiveness. Meanwhile, whether or not there is capital intensity or financial distress cannot encourage a company to engage in tax aggressiveness.